Balancing education, training and the market: a comparative analysis of current curricula for Master's programmes in translation between English and Chinese in China and the UK - Hu, Wan (2015)
The global market forces have had a strong influence on Higher Education. Universities worldwide have been largely commercialised. Despite a number of work that has been published on the relationship between universities and the market, limited research has been done in examining and comparing the impact of market forces on the degree courses in different countries, especially in the case of Translation Studies.